Origin and management of neotropical cassava arthropod pests - Bellotti, Anthony C.; Braun, Ann R.; Arias, B.; Castillo Franco, J.A.; Guerrero, J.M. (1994)
Cassava, one of the world's major food crops is grown throughout the tropical regions of the world. Cassava originated in the neotropics; it was introduced into West Africa from Brazil by slave traders in the 1500's, and taken to Asia during the 17th century. Consequently the greatest diversity of cassava pests, as well their natural enemies is found in the neotropics. Several species depress yield significantly; these include mites ( Mononychellus check for this species in other resources spp.), mealybug ( Phenacoccus herreni check for this species in other resources ), the cassava hornworm ( Erinnyis ello check for this species in other resources ), the burrowing bug ( Cyrtomenus bergi check for this species in other resources ), whiteflies ( Aleurotrachelus socialis check for this species in other resources , Aleurothrixus aepim check for this species in other resources ), thrips ( Frankliniella williamsi check for this species in other resources ), and lacebugs ( Vatiga manihotae check for this species in other resources , V. illudeus and Amblystria machalana check for this species in other resources ). Mites, mealybugs, thrips and lacebugs attack cassava primarily during dry periods, causing severe leaf necrosis. The hornworm will feed on cassava leaves throughout the long growing cycle of the crop, although severe attacks usually coincide with the onset of rains. Burrowing bugs feed directly on cassava roots, rendering them unacceptable for the commercial market. In the early 1970's, the cassava green mite, Mononychellus tanajoa check for this species in other resources and the cassava mealybug P. manihoti were inadvertently introduced to Africa from the neotropics. These pests have since spread throughout most of the cassava-growing regions of Africa, causing severe crop losses. The unauthorized movement of cassava germplasm, between and within continents, involves a risk of accidentally introducing additional pests. Control strategies are based on host plant resistance, biological control and cultural practices. Adequate levels of resistance have been identified for mite and whiteflies and moderate levels for mealybugs. Burrowing bug damage is less on varieties with high HCN concentration. Many species of natural enemies have been identified for mites, mealybugs and the cassava hornworm. A granulosis virus is effective in the management of hornworm populations. Chemical pesticide application to control cassava pests is discouraged and efforts are being made to develop Integrated Pest Management (IPM) programmes which do not incorporate pesticide use.